2004
DOI: 10.1590/s0074-02762004000600014
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi: establishment of permeable cells for RNA processing analysis with drugs

Abstract: Pre-mRNA maturation in trypanosomatids occurs through a process called trans-splicing which involves excision of introns and union of exons in two independentIn the process of pre-mRNA maturation, known as splicing, the introns (non-coding regions of polypeptides) are removed from primary transcripts and the exons (coding regions) joined to form a contiguous sequence specifying a functional polypeptide. It was observed that the process is dependent on ribonucleoproteins, small molecules of RNA binding proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…These results are compatible with those reported by Ambrosio et al (19) and in addition suggest that somehow trans-splicing can also be affected in these parasites, since some RNA bands in the gels are related to the small nuclear RNAs involved in this mechanism (20).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are compatible with those reported by Ambrosio et al (19) and in addition suggest that somehow trans-splicing can also be affected in these parasites, since some RNA bands in the gels are related to the small nuclear RNAs involved in this mechanism (20).…”
Section: Discussionsupporting
confidence: 93%
“…However, the results obtained thus far show that this interference still promotes the trans-splicing reaction in the cells but at a lower rate than observed in the control, indicating that the drug activity did not completely abolish the trans-splicing reaction (19).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Trans-splicing participates in the processing of polycistronic transcription units into individual mRNAs in which a short transcript spliced leader (SL RNA) is trans-spliced to the acceptor premRNA, giving origin to the mature mRNA. We showed that NFOH-121 affected the RNA processing and the trans-splicing reaction, even though at lower intensity (19).…”
Section: Discussionmentioning
confidence: 81%
“…Ambrósio and co-workers (2004) demonstrated that standardization of trans-splicing reaction with T. cruzi epimastigote forms (Y strain) permeable cells facilitates the study of RNA processing in these trypanosomatids and can be used as a model of study drug activity on trans splicing mechanism. The authors also demonstrated that pro-drug NFOH-121, derived from nitrofurans (Chung et al, 2003), was able to interfere with RNA processing this parasite, although the reaction of trans-splicing has not been affected (Ambrósio et al, 2004). The nitrofurans are compounds with the capacity to inhibit trypanotiona reductase, an important enzyme involved in the antioxidant metabolism of T. cruzi.…”
Section: Wwwintechopencommentioning
confidence: 99%